2014
DOI: 10.1590/0037-8682-0036-2014
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-transplant Epstein-Barr virus-related lymphoproliferative disease in solid organ and hematopoietic stem cell recipients

Abstract: Epstein-Barr virus (EBV)-related post-transplant lymphoproliferative disease (PTLD) is one of the most serious complications associated with solid organ and hematopoietic stem cell transplantation. PTLD is most frequently seen with primary EBV infection post-transplant, a common scenario for pediatric solid organ recipients. Risk factors for infection or reactivation of EBV following solid organ transplant are stronger immunosuppressive therapy regimens, and being seronegative for receptor. For hematopoietic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In clinical practice, we have found that there are many reasons that can lead to increased uptake of 18 F-FDG in tonsils, posterior pharyngeal wall, or adenoids, such as a high EBV DNA load or tonsil hypertrophy. 31,32 Moreover, 18 F-FDG uptake also increases in patients with other conditions after transplantation, such as postoperative inflammation, infection, bone marrow activation, or transplant rejection. 19 Therefore, we used the ratio of SUVmaxBio to SUVmaxTon to numerically validate our reasoning in the above clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, we have found that there are many reasons that can lead to increased uptake of 18 F-FDG in tonsils, posterior pharyngeal wall, or adenoids, such as a high EBV DNA load or tonsil hypertrophy. 31,32 Moreover, 18 F-FDG uptake also increases in patients with other conditions after transplantation, such as postoperative inflammation, infection, bone marrow activation, or transplant rejection. 19 Therefore, we used the ratio of SUVmaxBio to SUVmaxTon to numerically validate our reasoning in the above clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there was a statistical difference in SUVmax between PTLD‐negative and nondestructive PTLD cases, the sensitivity, specificity, PPV, NPV, and accuracy obtained using this index were poor. In clinical practice, we have found that there are many reasons that can lead to increased uptake of 18 F‐FDG in tonsils, posterior pharyngeal wall, or adenoids, such as a high EBV DNA load or tonsil hypertrophy 31,32 . Moreover, 18 F‐FDG uptake also increases in patients with other conditions after transplantation, such as postoperative inflammation, infection, bone marrow activation, or transplant rejection 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, many authors discuss the cost-effectiveness of EBV monitoring once-a-week and therefore many studies are required to show what would be the best time and interval of monitoring. Moreover, EBV viral load has been having different input data since the cutoff viral loads for treatment are variable and the development of international standardization of EBV viral load management is yet to be defined (12,13,26). Gulley and Tang, affirm that routine monitoring of EBV infection is viable in PTLD prevention, although further studies must be done to correlate specific viral loads in the identification of high-risk patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…Despite low to moderate sensitivity and negative predictive value for the detection of PTLD at diagnosis, 18 F-FDG PET/CT retains clinical utility in the management of pediatric PTLD patients. Due to the high number of false-negative scans in the tonsils/adenoids, physicians must remain alert for signs that might indicate the presence of disease, such as high Epstein-Barr virus DNA load and tonsillar hypertrophy (4,33). Nevertheless, if a biopsy is positive for non-destructive PTLD in the tonsils/adenoids but the 18 F-FDG PET/CT is interpreted as PTLD-negative, it may indicate that the disease is focal and therapy may be limited to reduction of immunosuppression (or potentially rituximab) and clinical followup.…”
Section: F-fdg Pet/ct For Response Assessmentmentioning
confidence: 99%